Investigation of the complete supply chain management for potatoes in Northern Ireland (Journal of the Bangladesh Agricultural University, 2012)
Supply Chain Management (SCM) is an integral approach of management where lots of beneficiaries work together with their professional interest. Potatoes supply chain like other agricultural products in developed country like the  United Kingdom included some important beneficiaries. Interests are not same due to the nature of the professional  activity. In distribution systems in developed country always have problems to organise all beneficiaries. Some beneficiaries are discriminated some are not their status as profitable either company or sole trader. In the study,  potato farmers of Northern Ireland produce potatoes and these potatoes supposed to be distributed directly to the consumers. As the work in the capitalist society divided in many ways with profit motive, therefore there were many intermediaries between producers and consumers who worked for distributing NI potato to the consumers. They were related together with their own interest and goal. One beneficiary was not thinking about another beneficiary with any  kind of interest sacrifice. Finally farmers who were the main producers became discriminated with the price. This is the main problem found in the study. Consumers also have no intention to know the life of farmers. If farmers societyis not survived in sustainable development way then the potatoes will not be cultivated. Therefore in potatoes farming  everybody in the society needs to make their attention for the right of the potatoes farmers of NI.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12104   J. Bangladesh Agril. Univ. 10(1): 125132, 2012